2016
DOI: 10.1038/srep26494
|View full text |Cite
|
Sign up to set email alerts
|

ICOS+PD-1+CXCR3+ T follicular helper cells contribute to the generation of high-avidity antibodies following influenza vaccination

Abstract: The immune mechanism leading to the generation of protective antibody responses following influenza trivalent inactivated vaccine (TIV) vaccinations remains largely uncharacterized. We recently reported that TIV vaccination induced a transient increase of circulating ICOS+PD-1+CXCR3+ T follicular helper (cTfh) cells in blood, which positively correlated with the induction of protective antibody responses measured at day 28. However, whether and how these T cells directly contribute to antibody response remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
153
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 25 publications
9
153
0
Order By: Relevance
“…Previous studies have reported the positive correlation between the number of GC B cells and Tfh cells [26, 27]. Further, in humans Tfh helper cells have been reported to contribute to the production of high affinity antibodies following influenza vaccination [28]. Thus, one approach to achieve higher quality antibody is provision of additional modulatory signals that promote Tfh, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the positive correlation between the number of GC B cells and Tfh cells [26, 27]. Further, in humans Tfh helper cells have been reported to contribute to the production of high affinity antibodies following influenza vaccination [28]. Thus, one approach to achieve higher quality antibody is provision of additional modulatory signals that promote Tfh, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…112,123 In addition to chemokine receptor expression, cTfh cells can also be divided into "activated" and "resting" subsets based on PD-1 expression, with the PD-1 hi "activated" population most efficiently promoting B cell differentiation into antibodysecreting cells with IgG production. 112,123 In addition to chemokine receptor expression, cTfh cells can also be divided into "activated" and "resting" subsets based on PD-1 expression, with the PD-1 hi "activated" population most efficiently promoting B cell differentiation into antibodysecreting cells with IgG production.…”
Section: Tfh Cell S In the B Loodmentioning
confidence: 99%
“…Of note, cTfh are not all identical in their transcriptional profile or ability to provide B cell help 124 . Circulating Tfh have been described as being polarized towards Th1, Th2, and Th17 cells, while cTfh that express ICOS and other markers of activation have been shown to contain vaccine-specific responses 36,84,120,124 . Moving forward, it will be critical to define the ways in which cTfh can reflect the ongoing lymph node biology of HIV infection and immune dysfunction.…”
Section: Cd4+ T Cells In Human and Non-human Primate Chronic Viral Inmentioning
confidence: 99%